2015
DOI: 10.3390/nu7075257
|View full text |Cite
|
Sign up to set email alerts
|

High Dietary Fat Intake during Lactation Promotes the Development of Social Stress-Induced Obesity in the Offspring of Mice

Abstract: This study examined how a maternal high-fat diet (HD) during lactation and exposure of offspring to isolation stress influence the susceptibility of offspring to the development of obesity. C57BL/6J mice were fed a commercial diet (CD) during pregnancy and a CD or HD during lactation. Male offspring were weaned at three weeks of age, fed a CD until seven weeks of age, and fed a CD or HD until 11 weeks of age. Offspring were housed alone (isolation stress) or at six per cage (ordinary circumstances). Thus, offs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
25
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 25 publications
(32 citation statements)
references
References 29 publications
5
25
2
Order By: Relevance
“…Moreover, the weaning weight of offspring (3‐week‐old) increased, and lipid accumulation in the liver tissue was observed in the HF‐diet‐fed animals during lactation, consistent with a previous study (Tsuduki, Yamamoto, E, Hatakeyama, & Sakamoto, ). The accumulation of lipids in the liver suggests possible interference with mitochondrial and microsomal function leading to disruption in lipoprotein transport and fatty acid accumulation and metabolism (Khan et al, ).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Moreover, the weaning weight of offspring (3‐week‐old) increased, and lipid accumulation in the liver tissue was observed in the HF‐diet‐fed animals during lactation, consistent with a previous study (Tsuduki, Yamamoto, E, Hatakeyama, & Sakamoto, ). The accumulation of lipids in the liver suggests possible interference with mitochondrial and microsomal function leading to disruption in lipoprotein transport and fatty acid accumulation and metabolism (Khan et al, ).…”
Section: Discussionsupporting
confidence: 91%
“…Indeed, it was shown that the serum parameters that were altered by a maternal HF diet exhibited inconsistencies in male and female pups, highlighting the sexspecific feature of the response to nutrition intervention. Moreover, the weaning weight of offspring (3-week-old) increased, and lipid accumulation in the liver tissue was observed in the HF-diet-fed animals during lactation, consistent with a previous study (Tsuduki, Yamamoto, E, Hatakeyama, & Sakamoto, 2015). The accumulation of lipids in the liver suggests possible interference with mitochondrial and microsomal function leading to disruption in lipoprotein transport and fatty acid accumulation and metabolism (Khan et al, 2003).…”
Section: Discussionsupporting
confidence: 89%
“…Biochemical analyses of serum and liver samples were performed as described previously. [11,12] Serum and liver triacylglycerol, total cholesterol, and serum LDL cholesterol (LDL-C), HDL cholesterol (HDL-C), phospholipid and glucose levels were measured using commercial enzyme kits (Wako Pure Chemical, Osaka, Japan). Serum insulin was determined by ELISA (Morinaga Institute of Biological Science, Kanagawa, Japan).…”
Section: Serum and Liver Biochemical Analysismentioning
confidence: 99%
“…Biochemical analyses of serum and liver samples were performed as described previously. [24,25] Serum and liver triacylglycerol (TG), total cholesterol (TC), and serum phospholipid (PL), glucose, alanine aminotransferase (ALT), and aspartate transaminase (AST) levels were measured using commercial enzyme kits (Wako Pure Chemical, Osaka, Japan). Serum insulin was determined using an ELISA kit (Morinaga Institute of Biological Science, Yokohama, Japan).…”
Section: Serum and Liver Biochemical Analysismentioning
confidence: 99%